Influences of communication ability, organizational intimacy, and trust among colleagues on job satisfaction of nurses in comprehensive nursing care service units - Hahm, Sue Young; Gu, Minkyung; Sok, Sohyune (Frontiers in Public Health, 2024)
Background: Communication abilities, organizational intimacy, trust among colleagues, and job satisfaction of nurses in comprehensive nursing care service units are emphasized more than any other ward, and research on this is necessary. Objective: The study was to examine the influences of communication ability, organizational intimacy, and trust among colleagues on job satisfaction of nurses in the comprehensive nursing care service units. Methods: This study used a cross-sectional descriptive design. The participants were 155 nurses caring for patients in the comprehensive nursing care service units in Seoul. Measures included the general characteristics of study participants, communication ability, organizational intimacy, trust among colleagues, and job satisfaction. Data was analyzed using SPSS/WIN version 27.0 program. Data collection period was from August to September, 2022. Results: Factors influencing job satisfaction of nurses at the comprehensive nursing care service units was organizational intimacy (β = 0.36), communication abilities (β = 0.26), trust among colleagues (β = 0.22), and the average number of patients assigned to a nurse (β = -0.19), which explained 67% of the variance. Conclusions: Organizational intimacy was the greatest factor influencing job satisfaction of nurses in the comprehensive nursing care service units. In order to increase the job satisfaction of ward nurses working in the comprehensive nursing care service, securing manpower is required, and it is necessary to provide effective nursing care with an average number of patients of 5 or less. In particular, a systematic job training program is needed to increase organizational intimacy within the team nurses.